2010
DOI: 10.1007/s10551-010-0454-9
|View full text |Cite
|
Sign up to set email alerts
|

The Exercise of Moral Imagination in Stigmatized Work Groups

Abstract: ABSTRACT. This study introduces the concept of moral imagination in a work context to provide an ethical approach to the controversial relationships between dirty work and dirty workers. Moral imagination is assessed as an essential faculty to overcome the stigma associated with dirty work and facilitate the daily work lives of workers. The exercise of moral imagination helps dirty workers to face the moral conflicts inherent in their tasks and to build a personal stance toward their occupation. Finally, we ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 57 publications
0
17
0
3
Order By: Relevance
“…Research on stigma is reported mainly in the health and psychology literatures where studies are conducted to examine the nature, impact of, and coping strategies used to deal with stigma in a variety of life contexts (Roca 2010). These contexts include physical (Fife and Wright, 2000) and mental illness (Kroska and Harkness 2006;Markowitz 1998), sexual orientation (Hereck et al, 2009), and criminality (Rasmusen1996; Schnittker and John 2007).…”
Section: Background Literaturementioning
confidence: 99%
“…Research on stigma is reported mainly in the health and psychology literatures where studies are conducted to examine the nature, impact of, and coping strategies used to deal with stigma in a variety of life contexts (Roca 2010). These contexts include physical (Fife and Wright, 2000) and mental illness (Kroska and Harkness 2006;Markowitz 1998), sexual orientation (Hereck et al, 2009), and criminality (Rasmusen1996; Schnittker and John 2007).…”
Section: Background Literaturementioning
confidence: 99%
“…Participam do universo do trabalho sujo aquelas atividades que envolvem objetos física, moral ou socialmente degradantes e que remetem a uma experiência tabu, impura, contagiada, indesejável, além de sustentarem indicadores de desprestígio social (Hughes, 1962;Butler, Chillas & Muhr, 2012;Mattos, 2012). Não obstante, Hughes esclarece que a noção de trabalho sujo não se refere a algo escuso, torpe ou ilegal; ao contrário, o trabalho sujo se refere a atividades que são necessárias e benéficas para a coletividade, mas carregam consigo marcas de uma construção social que lhes impingiu características repulsivas, a ponto de o olhar do outro tender a identificar esse trabalhador ao objeto de seu trabalho (Hughes, 1962;Emerson & Pollner, 1976;Ashforth & Kreiner, 1999;Roca, 2010;Mattos, 2012;Barros & Lhuilier, 2013). No universo das atividades tipificadas como trabalho sujo, focalizamos neste artigo a atividade dos necrotomistas, que são servidores policiais que auxiliam na realização de necropsias (ou perícias necroscópicas) em departamentos ou institutos de medicina legal.…”
Section: Palabras-claveunclassified
“…Moberg and Seabright (2000) suggest several benefits to moral imagination: enlarging one's ability to identify possible courses of action by transcending scripts and common moral boundaries; developing moral mindfulness; fine-tuning one's relation to moral rules to determine when they should be universally binding and when they should allow for flexibility; elaborating and assessing "possible selves" (Markus and Nurius, 1986) that reinforce intentions through both social and self-sanctions and motivations. Roca (2010) argues that moral imagination stimulates moral intuition (to develop a wider range of possible scenarios), fine-tunes moral judgement to align with one's moral identity, and allows one to envision new ways of approaching an issue through a "critical creativity". Applying the concept to socially "dirty jobs", Roca (2010) proposes that organisations can induce greater moral imagination by encouraging the expression of individuality and critical thinking, by building up knowledge of one's community to understand 'others', and reassessing the content of job design.…”
Section: Practical Implications For Decision-makingmentioning
confidence: 99%
“…Roca (2010) argues that moral imagination stimulates moral intuition (to develop a wider range of possible scenarios), fine-tunes moral judgement to align with one's moral identity, and allows one to envision new ways of approaching an issue through a "critical creativity". Applying the concept to socially "dirty jobs", Roca (2010) proposes that organisations can induce greater moral imagination by encouraging the expression of individuality and critical thinking, by building up knowledge of one's community to understand 'others', and reassessing the content of job design. She also notices that narratives are useful in enhancing awareness of complex issues.…”
Section: Practical Implications For Decision-makingmentioning
confidence: 99%